Analysis of vibration machine parameters affecting compaction quality - Vasiliev, Oleksii; Yakovenko, Andrii (Academic journal Industrial Machine Building Civil Engineering, 2023)
Compaction of products is an important stage of construction work and engineering projects. It has a significant impact on the stability and reliability of the construction. However, the compacting quality of the products depends on various parameters that are controlled and adjusted on vibration machine. Analysis of these parameters will allow us to determine the optimal values to achieve the maximum quality of compacting products using a vibration machine. The article studies the influence of different parameters of the vibration machine on the quality of the material compaction. The purpose of this article is to determine the choice of the optimal design of vibration machine, depending on the specific conditions of production and the size of reinforced concrete products. The authors emphasise on such key factors as vibration amplitude, frequency, workload and duration of exposure. Therefore, taking into account the fact that these parameters can help to understand better the vibration compaction process and develop optimal conditions for achieving high quality material compaction. This study presents the most rational design scheme of a small-sized vibration machine and its optimal dynamic parameters. The results of this study will be interesting for engineers, construction contractors and specialists who are engaged in the design or working on compaction of products
Keywords: vibration; vibration oscillation amplitude; vibration exciter; vibration machine; debalance; forced oscillations